Woody molding having wood grain and method for producing same

By impregnating wooden materials with hardened resin and controlling gap ratios, the method addresses the issue of high density and plastic-like tactile sensation in conventional moldings, resulting in wooden moldings with a wood-like feel and appearance.

JP7624638B2Active Publication Date: 2025-01-31NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023521252
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-14
Filing Date
2022-05-12
Publication Date
2025-01-31
Estimated Expiration
2042-05-12

AI Technical Summary

Technical Problem

Conventional methods for manufacturing wooden moldings result in crushed wood cell cavities, leading to a high density and a tactile sensation more akin to plastic rather than wood.

Method used

A method involving impregnating wooden materials with hardened resin, followed by loading and curing the resin in a mold to create a wooden molding with controlled gap ratios and resin distribution, mimicking the tactile sensation of wood.

Benefits of technology

The method efficiently produces wooden moldings with a tactile sensation and appearance similar to natural wood, suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624638000008
    Figure 0007624638000008
  • Figure 0007624638000009
    Figure 0007624638000009
  • Figure 0007624638000010
    Figure 0007624638000010
Patent Text Reader

Abstract

The woody molded article (10) according to the present invention includes a woody material and a cured resin, the proportion of voids (void ratio) derived from ligneous cell lumens of the woody material that are present inside the woody molded article (10) being 5-60%, and the difference in void ratio between one region (12) and another region (14), which are positioned at mutually different depths from the surface toward the interior, being 15 points or lower. The method for producing a woody molded article according to the present invention comprises, in order: a resin-impregnated-material preparation step for preparing a resin-impregnated material by impregnating a woody raw material with a curable resin; a load application step for disposing the resin-impregnated material inside a die and applying a load to the resin-impregnated material; a load removal step for removing the load before the curable resin included in the resin-impregnated material, which is in a compressed state inside the die, solidifies; and a resin curing step for curing the curable resin to obtain a woody molded article.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a woody molded product that contains a wood material and a hardened resin and has a texture similar to that of wood, and to a method for efficiently producing a woody molded product that has a texture similar to that of wood and has an excellent woody appearance. [Background technology]

[0002] Conventionally, there has been known a technique for producing a wood-based molded body by converting renewable wood logs, waste wood, or recycled materials into powder, fibers, chips, etc., and then placing the resulting material, together with resin if necessary, into a cavity of a mold and compressing and molding the material under heated conditions (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 11-300711 [Patent Document 2] JP 2010-155394 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the conventional methods described above, when compression molding is performed, the mixed raw material in the mold is clamped with a maximum pressure stroke or a load close to it, which often results in the wood cell cavities of the wood raw material being crushed and densified, resulting in a wood molded product with a feel similar to that of plastic. An object of the present invention is to provide a woody molded product that contains a wood material and a hardened resin and has a texture similar to that of wood. Another object of the present invention is to provide a method for efficiently producing a woody molded product that has a texture similar to that of wood and has an excellent woody appearance. [Means for solving the problem]

[0005] The inventors have impregnated a small piece of wood raw material with a hardening resin to prepare a resin-impregnated material, filled the obtained resin-impregnated material into a mold, and then applied a load to the resin-impregnated material. The load is then removed before the hardening resin contained in the resin-impregnated material, which is in a compressed state inside the mold, solidifies, and then the hardening resin is hardened by applying a molding method. This has enabled the inventors to obtain a wood molded product with a texture similar to wood and excellent wood-like appearance because the voids originating from the wood cell cavities of the wood raw material do not disappear completely, but remain at a specific ratio (porosity).

[0006] The present invention is illustrated below. (1) A wood-based molding containing a wood material and a hardened resin, A wood molding characterized in that, inside the wood molding, the porosity originating from the wood cell cavities of the wood material is 5 to 60%, and the difference in porosity between one region and another region located at different depths from the surface toward the inside is 15 points or less. (2) A wood molding as described in (1) above, in which the porosity inside the wood molding, originating from the wood cell cavities of the wood material, is 5 to 50%, and the difference between the porosity in a region between 0.01 mm and 1 mm deep from the surface of the wood molding and the porosity deep inside, more than 1 mm from the surface of the wood molding, is 11 points or less. (3) The woody molding according to (1) or (2) above, wherein the cured resin is derived from a thermosetting resin. (4) A method for producing the woody molding according to any one of (1) to (3) above, A resin-impregnated material preparation step of impregnating a wood raw material with a curable resin to prepare a resin-impregnated material; a load application step of placing the resin-impregnated material in a mold and applying a load to the resin-impregnated material; a load-removing step of removing a load from the resin-impregnated material before the curable resin contained in the resin-impregnated material in a compressed state within the mold is solidified; a resin curing step of curing the curable resin to obtain the woody molded body; A method for manufacturing a woody molded product, comprising the steps of: Hereinafter, this manufacturing method will be referred to as "first method." (5) A method for manufacturing a wood molded body as described in (4) above, in which, in the load application process, a load is applied to the resin-impregnated material until the material becomes smaller than the wood molded body, and in the unloading process, the load is unloaded until the material in the mold assumes the desired shape of the wood molded body. (6) The method for producing a woody molded product according to (4) or (5) above, wherein the curable resin is a thermosetting resin, and the load application step and the load removal step are carried out under heating conditions. (7) A method for producing the woody molding according to any one of (1) to (3) above, A resin-impregnated material preparation step of impregnating a wood raw material with a curable resin to prepare a resin-impregnated material; a load application step of placing the resin-impregnated material in a mold and applying a load to the resin-impregnated material; a load-removing step of removing a load from the resin-impregnated material before the curable resin contained in the resin-impregnated material in a compressed state within the mold is solidified; a load reapplication step of applying a load to the resin-impregnated material before the curable resin solidifies; a resin curing step of curing the curable resin to obtain the woody molded body; A method for manufacturing a woody molded product, comprising the steps of: Hereinafter, this manufacturing method will be referred to as the "second method." (8) A method for manufacturing a wood molded body as described in (7) above, in which, in the load application process, a load is applied to the resin-impregnated material until the material becomes smaller in size than the wood molded body, and in the unloading process, the load is unloaded until the material in the mold becomes a shape larger than the desired wood molded body. (9) The method for producing a woody molded body according to (7) or (8) above, wherein the curable resin is a thermosetting resin, and the load application step, the unloading step, and the load reapplication step are carried out under heating conditions. (10) The method for producing a woody molded product according to any one of (4) to (9) above, wherein the woody raw material contains wood chips. Effect of the Invention

[0007] The woody molded product of the present invention has a texture similar to that of wood and can therefore be widely used for daily necessities, furniture, building materials, construction components, electrical appliances or audio equipment casings, vehicle components, etc. According to the manufacturing method of the woody molded product of the present invention (first method and second method), it is possible to efficiently manufacture a woody molded product having a texture similar to that of wood and excellent woody appearance. Furthermore, according to the first method, it is possible to manufacture a woody molded product having a small color difference ΔE from the wood raw material. According to the second method, it is possible to efficiently manufacture a woody molded product having a higher gloss than the first method. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a schematic cross-sectional view showing measurement regions at different depths from the surface toward the inside when measuring the porosity originating from wood cell cavities of a wood material in a wood molded body of the present invention. [Diagram 2] These are schematic cross-sectional views of wood cells cut perpendicular to their longitudinal direction, where (X) is an example of a normal wood cell, (Y) is an example of a wood cell in a wood molded product of the present invention that has been shear-deformed, and (Z) is an example of a wood cell in a wood molded product of the present invention that has been buckled. [Diagram 3] 4 is a graph showing an example of a press schedule (change in punch stroke) after a load application step in the first method for producing a woody molded body of the present invention. [Figure 4] 4 is a graph showing an example of a press schedule (change in punch stroke) after the load application step in the second method for producing a woody molded body of the present invention. [Diagram 5] 1 is a graph showing the press schedule (changes in punch stroke) applied when producing woody molded articles in Examples 1 to 13. [Figure 6] 1 is a surface image of the woody molded product (C1) obtained in Example 1. [Figure 7] 1 is a cross-sectional image of a surface layer of the woody molded product (C1) obtained in Example 1. [Figure 8] This is the binarized image of FIG. [Figure 9] 1 is a cross-sectional image of the inside of the wood molded product (C1) obtained in Example 1. [Figure 10] This is the binarized image of FIG. [Figure 11] 2 is an enlarged cross-sectional image of the inside of the wood molded product (C1) obtained in Example 1. [Figure 12] 1 is a graph showing the press schedule (changes in punch stroke) applied when producing a woody molded body in Comparative Example 1. [Figure 13] 1 is a surface image of the woody molded product (C2) obtained in Comparative Example 1. [Figure 14] 1 is a cross-sectional image of a surface layer of a woody molded product (C2) obtained in Comparative Example 1. [Figure 15] 1 is a cross-sectional image of the inside of the wood molded product (C2) obtained in Comparative Example 1. [Figure 16] 1 is an enlarged cross-sectional image of the inside of the wood molded product (C2) obtained in Comparative Example 1. [Figure 17] 1 is a graph showing the press schedule (changes in punch stroke) applied when producing woody molded articles in Comparative Examples 2 to 7. [Figure 18] 1 is a surface image of the woody molded product (C3) obtained in Comparative Example 2. [Figure 19] 1 is a surface image of the woody molded product (D1) obtained in Example 2. [Figure 20] 1 is a cross-sectional image of the surface layer of the woody molded product (D1) obtained in Example 2. [Figure 21] 1 is a surface image of the woody molded product (D2) obtained in Example 3. [Figure 22] 1 is a surface image of the woody molded product (D3) obtained in Example 4. [Figure 23] 1 is a surface image of the woody molded product (D4) obtained in Comparative Example 3. [Figure 24] 1 is a cross-sectional image of the surface layer of the woody molded product (D4) obtained in Comparative Example 3. [Diagram 25] 1 is a surface image of the woody molded product (E1) obtained in Example 5. [Figure 26]1 is a surface image of the woody molded product (E2) obtained in Example 6. [Figure 27] 1 is a cross-sectional image of the surface layer of the woody molded product (E2) obtained in Example 6. [Figure 28] 1 is a surface image of the woody molded product (E3) obtained in Example 7. [Figure 29] 1 is a surface image of the woody molded product (E4) obtained in Comparative Example 4. [Diagram 30] 1 is a surface image of the woody molded product (F1) obtained in Example 8. [Diagram 31] 1 is a surface image of the woody molded product (F2) obtained in Example 9. [Diagram 32] 1 is a surface image of the woody molded product (F3) obtained in Example 10. [Diagram 33] 1 is a surface image of the woody molded product (F4) obtained in Comparative Example 5. [Diagram 34] 1 shows surface images of the woody molded products (H1), (H2), and (H3) obtained in Examples 13 and 14 and Comparative Example 7. [Diagram 35] FIG. 17 is a schematic diagram illustrating a method for producing a composite 51 in Example 15, in which an adherend portion 42 derived from a prepreg 41 and a wood molded body portion 47 are joined together. [Diagram 36] 13 is an image (surface image) of the upper surface side of a woody molded body portion 47 in a composite body 51 obtained in Example 15. [Figure 37] 1 is a backside image of a composite 51 obtained in Example 15 (a front side image of an adherend portion 42). [Figure 38] 13 is an image (surface image) of the upper surface side of a woody molded body portion 47 in a composite body 51 obtained in Comparative Example 8. [Figure 39] 1 is a backside image of a composite 51 obtained in Comparative Example 8 (a front side image of an adherend portion 42). [Diagram 40] 1 is a graph showing the press schedule (changes in punch stroke) applied when producing the woody molded product (J1) in Example 16. [Diagram 41] 1 is an oblique image of the woody molded product (J1) obtained in Example 16. [Diagram 42] 1 is a graph showing the press schedule (changes in punch stroke) applied when producing the woody molded product (J2) in Example 17. [Diagram 43] 1 is an oblique image of the woody molding (J2) obtained in Example 17. [Diagram 44] 1 is a graph showing the press schedule (changes in punch stroke) applied when producing a woody molded product (J3) in Comparative Example 9. [Diagram 45] 1 is a perspective image of the woody molded product (J3) obtained in Comparative Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The woody molded product of the present invention includes a wood material and a hardened resin, and has a porosity derived from the wood cell lumen of the wood material, i.e., a ratio of voids (void portions) derived from the wood cell lumen, of 5-60% inside the woody molded product, and the difference in porosity between a first region and another region located at different depths from the surface toward the inside is 15 points or less. If the measured porosity in the first region and the porosity in the other regions are W1 (%) and W2 (%), respectively, the difference in porosity is expressed as |W1-W2| (%), and in the present invention, the unit of this |W1-W2| is expressed as "points".

[0010] The above-mentioned woody materials are derived from plants having woody cells, such as wood (conifers such as cedar, cypress, and pine; broad-leaved trees such as poplar, beech, oak, and birch), bamboo, flax (jute, kenaf, flax, hemp, ramie, sisal, and the like), and herbaceous plants, and may be either the plant itself, waste materials thereof, or chemically treated or crushed products thereof. The woody molded product of the present invention containing such woody materials is preferably an aggregate of at least one of fibers, powder, small pieces, and the like, all of which are not limited in shape and size.

[0011] The cured resin is at least one type of curable resin (such as a thermosetting resin, a room temperature curable resin, or a photocurable resin) selected from the group consisting of phenolic resin, epoxy resin, unsaturated polyester, urea resin, melamine resin, diallyl phthalate, silicon resin, vinyl ester resin, polyimide, and polyurethane, which has a crosslinked structure, either alone or by the action of a curing agent.

[0012] The above-mentioned hardened resin usually bonds adjacent pieces of wood material together, but in the wood molding of the present invention, the hardened resin is contained within some or all of the wood cell cavities and within the cell walls that make up the wood material, forming appropriate voids, so that the hardened resin is not unevenly distributed overall, and every surface of the wood molding has a texture similar to that of wood, and has an excellent wood-like appearance.

[0013] The mass ratio of the wood material and the hardened resin contained in the wood molding of the present invention is not particularly limited, but in order to fully obtain the effects of the present invention, the content of the hardened resin is preferably 5 to 120 parts by mass, and more preferably 10 to 80 parts by mass, per 100 parts by mass of the wood material.

[0014] The woody molded product of the present invention may contain other materials in addition to the above-mentioned wood material and cured resin, such as plasticizers, antioxidants, UV absorbers, anti-aging agents, fillers, antibacterial agents, preservatives, antistatic agents, curing accelerators, dyes, pigments, etc.

[0015] The woody molded product of the present invention is preferably a compression molded product containing at least one of a woody material, such as fiber, powder, and small pieces, and a hardened resin, and having a deformed cell wall. The porosity derived from the woody cell lumen of the woody material, which is a raw material for producing the woody molded product of the present invention, is usually 20% or more, with an upper limit of 95%, but the porosity inside the woody molded product of the present invention containing a hardened resin is smaller than that of the raw material for production, being 5% or more, with an upper limit of 60%, because the hardened resin is contained in some or all of the woody cell lumen constituting the woody material while forming appropriate voids, as described above. This porosity is preferably 5 to 50%, more preferably 20 to 50%. The above-mentioned "inside of the woody molded product" means an inside that is 0.01 mm or more deep from the surface of the woody molded product.

[0016] In the present invention, the porosity is determined by cutting the woody molded product perpendicular to the longitudinal direction of the wood cells and observing the resulting cross section with a microscope (observation area: at least 0.5 mm 2 ) and binarizing the voids originating from the xylem cells lumen and the other parts based on the difference in brightness in the image, and calculating the area ratio of the voids. Details are described in the Examples below.

[0017] In the present invention, there is no significant difference in the porosity measurement position within the wood molded body. That is, the difference in porosity between one region and another region located at different depths from the surface of the wood molded body toward the inside is 15 points or less, preferably 13 points or less, and more preferably 11 points or less. The lower limit is usually 1 point. 1 is a schematic cross-sectional view showing two measurement regions at different depths from the surface toward the inside when measuring porosity, showing region 12 having a depth d1 as seen from the surface of wood molded body 10, and region 14 having a depth d2 as seen from the surface of wood molded body 10. The distance between region 12 and region 14 (distance as seen in the depth direction) is preferably at least 0.3 mm, and there is no particular limitation on the magnitude of the porosity in region 12 and the porosity in region 14.

[0018] In a particularly preferred embodiment of the present invention, the difference between the porosity in region 12 at a depth d1 of 0.01 to 1 mm from the surface of the wood molding and the porosity in region 14 at a depth d2 of more than 1 mm from the surface of the wood molding is 11 points or less.

[0019] In the woody molded product of the present invention, when a woody cell is cut perpendicular to its length and the cross section obtained is observed under a microscope in the same manner as in the sample preparation for measuring the porosity, it is preferable that the woody cells have a portion arranged in a curved or wavy line (see Figs. 7 to 10). Furthermore, the cell walls 22 of the woody cells 20 constituting the plant body or the like that is the raw material for producing the woody molded product are rounded polygonal as shown in Fig. 2 (X), circular, elliptical, etc. (see Fig. 16, for example). In contrast, in the woody molded product of the present invention, the woody cells 20 have a structure in which they are shear deformed and the cell walls 22 have a structure in which they are buckled deformed as shown in Fig. 2 (Y) and (Z) (see Fig. 12, for example). In the woody molded product of the present invention, as described above, the hardened resin is contained in the cell walls 22 and in the woody cell lumen 24 while forming appropriate voids, but the hardened resin portion present therein is not shown in Figs. 2 (Y) and (Z).

[0020] The first method for producing a wood molded body of the present invention sequentially comprises a resin-impregnated material preparation step of impregnating a wood raw material with a hardening resin to prepare a resin-impregnated material, a load application step of placing the obtained resin-impregnated material in a mold and applying a load to the resin-impregnated material, an unloading step of unloading the hardening resin contained in the resin-impregnated material in a compressed state within the mold before it solidifies, and a resin hardening step of hardening the hardening resin to obtain a wood molded body. The second method for producing a woody molded body of the present invention sequentially comprises a resin-impregnated material preparation step of impregnating a wood raw material with a curable resin to prepare a resin-impregnated material, a load application step of placing the obtained resin-impregnated material in a mold and applying a load to the resin-impregnated material, an unloading step of removing the load before the curable resin contained in the resin-impregnated material in a compressed state in the mold hardens, a load reapplication step of applying a load to the resin-impregnated material before the curable resin hardens, and a resin hardening step of hardening the curable resin to obtain a woody molded body. That is, the first and second methods of the present invention subject the resin-impregnated material placed in a mold to compression molding equipped with a specific means.

[0021] In the resin-impregnated material preparation steps according to the first and second methods, a resin-impregnated material is prepared by impregnating a wood raw material with a curable resin. The woody raw material may be any of the plants having woody cells themselves or waste materials thereof, or chemically treated or crushed products thereof, such as wood (conifers such as cedar, cypress, and pine; broad-leaved trees such as poplar, beech, oak, and birch), bamboo, flax (jute, kenaf, flax, hemp, ramie, and sisal), and herbaceous plants. The shape and size of the woody raw material are not particularly limited, and it may be at least one type selected from fibers, powder, small pieces (wood chips), and the like. Examples of the curable resin include phenol resin, epoxy resin, unsaturated polyester, urea resin, melamine resin, diallyl phthalate, silicon resin, vinyl ester resin, polyimide, polyurethane, etc. Among these, phenol resin and melamine resin are preferred. Furthermore, low molecular weight resins with a molecular weight of less than about 2000 are preferred because they are easily impregnated into the cell wall. Furthermore, water-soluble or alcohol-soluble resins are preferred.

[0022] In the resin-impregnated material preparation step, depending on the type of curable resin, a curing agent may be used in combination. When the curable resin is a phenolic resin, examples of the curing agent that can be used include amine-based curing agents such as aliphatic polyamines, aromatic polyamines, and diamine diamides; acid anhydride curing agents such as alicyclic acid anhydrides and aromatic acid anhydrides; and imidazole compounds. When the hardenable resin is a melamine resin, the hardener may be hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, acetic acid, formic acid, oxalic acid, or the like.

[0023] Furthermore, if necessary, lubricants, plasticizers, antioxidants, UV absorbers, antioxidants, fillers, antibacterial agents, preservatives, antistatic agents, curing accelerators, dyes, pigments, water, organic solvents such as alcohol, and the like can be used together with the curable resin. Examples of the lubricant include oxidized polyalkylene wax, acid-modified polyalkylene wax, etc. In the present invention, when the curable resin and the lubricant are used in combination, the deformation resistance of the resin-impregnated material obtained can be reduced and the moldability can be improved when the material is molded. In addition, the formation of voids in the molded body can be promoted in the unloading process, and the wood texture can be sufficiently imparted.

[0024] In the resin-impregnated material preparation step, the method of impregnating the wood raw material with the hardening resin is not particularly limited. However, in order to sufficiently fill the wood cell cavities and cell walls constituting the wood raw material with the hardening resin and to soften and deform the material in the mold in each subsequent step to efficiently obtain a desired shape, it is preferable to immerse the wood raw material in the hardening resin or its solution (usually an organic solution) under conditions (temperature, humidity, etc.) in which the hardening resin does not harden, and then leave it to stand. The standing time is not particularly limited, but is preferably 2 hours or more, more preferably 4 hours or more, and even more preferably 6 hours or more. When the wood raw material has a bulky shape, a method of injecting the hardening resin into the inside of the wood raw material by decompression, pressurization, etc. is preferable. The wood raw material and the hardening resin are used so that the amount of hardening resin used is preferably 5 to 120 parts by mass, more preferably 10 to 80 parts by mass, when the amount of the wood raw material used is 100 parts by mass.

[0025] The resin-impregnated material obtained by the resin-impregnated material preparation process has a composition according to the above-mentioned amounts of wood raw material and hardenable resin used, and is stored under conditions in which the hardenable resin does not harden until the load application process of the first method and until the load re-application process of the second method.

[0026] In the load application step according to the first and second methods, a load is applied to the resin-impregnated material placed in the mold. The number of resin-impregnated materials placed in the mold, the filling rate, and the applied load and application time are not particularly limited. The load (surface pressure) is preferably 1 to 500 MPa, more preferably 5 to 300 MPa. In order to obtain a woody molded body having a desired shape and size and excellent woody appearance as a final product, it is preferable to form an object (hereinafter referred to as a "precursor molded body") smaller than the desired woody molded body by applying a load in the load application step. Here, when multiple resin-impregnated materials are subjected to the load application step, the obtained precursor molded body is usually a lump. In this load application step, at least one of the resin-impregnated materials placed in the mold can form a precursor molded body smaller in size in at least one direction than the shape of the desired woody molded body by applying a load. Therefore, in the load application step, in order to obtain a desired precursor molded body, load application can be performed multiple times by changing the load application direction, angle, etc. under conditions that do not solidify the resin-impregnated material. Load application may also be performed from multiple directions at the same time.

[0027] In the unloading step of the first method, the precursor molded body in a compressed state in the mold is unloaded before the hardening resin contained therein solidifies, to obtain an unhardened wood molded body (hereinafter referred to as "unhardened wood molded body (M1)") preferably having the same shape and size as the final product. This "unloading" does not mean completely stopping the application of load to the precursor molded body and opening the mold, but reducing the load to guide the internal shape of the mold to the shape of the unhardened wood molded body (M1) having the desired shape and size. For example, if compression is performed using two molds, a first mold and a second mold, in the load application step, unloading can be performed in the unloading step while the resin-impregnated material is in contact with the inner surfaces of the first mold and the second mold, or while the resin-impregnated material is in contact with only one of the inner surfaces of the first mold and the second mold. The inventors believe that when the resin-impregnated material becomes compressed and fluidized by the load application step, most of the voids originating from the wood cell cavities are blocked, but by unloading in the unloading step, the cell walls are elastically restored, and an unhardened wood molded body (M1) is obtained in which the voids containing the unhardened hardenable resin are slightly restored, and these voids are maintained even after the resin hardening step. Note that, although the case where two molds are used has been described here, the number of molds used may be greater depending on the shape of the desired wood molded body.

[0028] In the present invention, when the shape of the woody molded product to be manufactured is not simple, the above-mentioned load application and unloading steps may be repeated.

[0029] In the resin hardening step of the first method, the hardenable resin contained in the unhardened wood molded body (M1) is hardened to obtain a wood molded body that contains a wood material and a hardened resin, has an internal ratio of voids originating from the wood cell cavities of the wood material (porosity) of 5 to 60%, and has excellent woody appearance. Depending on the type of hardenable resin, a hardening method for the hardenable resin, for example, a hardening method using heat, light, humidity, etc., and hardening conditions are selected.

[0030] In the case of the first method, the obtained woody molding has an excellent woody appearance, but the gloss of the surface may not be sufficient. Therefore, by using the second method, which includes a load reapplication step before the resin hardening step, the gloss can be improved. In the unloading step of the second method, similarly to the unloading step of the first method, when two molds, for example, a first mold and a second mold, are used, the resin-impregnated material can be unloaded while being in contact with the inner surface of the first mold and the inner surface of the second mold, or the resin-impregnated material can be unloaded while being in contact with only one of the inner surfaces of the first mold and the inner surface of the second mold. In the unloading step of the second method, it is preferable to perform unloading until the size of the space between the first mold and the second mold (the part filled with the resin-impregnated material) becomes larger than the size of the final product before the contained hardening resin solidifies, thereby producing an unhardened woody molding (hereinafter referred to as "unhardened woody molding (M2)") having a size larger than the final product.

[0031] In the load reapplication step of the second method, a load is applied to the uncured wood molded product (M2) in the mold before the curable resin solidifies, to obtain a wood molded product having a desired shape and size. The load and application time are not particularly limited, but the load (surface pressure) is preferably 0.5 to 20 MPa, more preferably 1 to 10 MPa.

[0032] In the resin hardening step of the second method, the hardenable resin contained in the unhardened wood molded body (M2) is hardened to obtain a wood molded body that contains a wood material and a hardened resin, has an internal ratio of voids originating from the wood cell cavities of the wood material (porosity) of 5 to 60%, and has excellent woody appearance and gloss. As in the first method, the hardening method and hardening conditions for the hardenable resin can be selected depending on the type of hardenable resin.

[0033] Next, a press schedule after the load applying step in the first and second methods will be described.

[0034] Figure 3 shows an example of a pressing schedule after the load application step in the first method, that is, a pressing schedule in which a molding machine equipped with a mold having a cavity that reflects the shape of a wood molded body is used, and a load application step is performed once to place a resin-impregnated material in the cavity of the mold and apply a load to obtain a precursor molded body that is smaller in size than the shape formed by the resin-impregnated material in at least one direction and is smaller than the shape formed by the resin-impregnated material, relative to the desired wood molded body (final product), and which then undergoes an unloading step to obtain an unhardened wood molded body (M1) preferably having the same shape and size as the final product, and a resin curing step to harden the curable resin contained in the unhardened wood molded body (M1), thereby producing a wood molded body having the desired size and shape.

[0035] The pressing schedule of FIG. 3 applies a load to the resin-impregnated material in the die until it is smaller than the desired wood body, i.e., the punch stroke S a For example, the compressed state with the maximum pressure (compression start time t1) is held for a certain time (holding time Δt1) until the precursor compact is formed (compression end time t2), and then the punch stroke S is set to a state where the internal structure of the die has a desired shape and size. b The load applied to the precursor compact is reduced by unloading (unloading time Δt2) until the unloading end time t3 is reached. b By maintaining this state for a certain period of time, the hardenable resin is completely hardened, thereby obtaining a wood molded product containing the wood material and the hardened resin.

[0036] In the first method, it is preferable to set the pressing schedule so that the hardening of the hardening resin starts at or after the unloading end time t3. It is also preferable to set the softening of the hardening resin and the cell walls impregnated with the hardening resin starts at or before the compression start time t1. It is necessary to soften and deform at least by the compression end time t2.

[0037] The press schedule in Figure 3 shows the relationship between molding time and punch stroke in order to carry out the preferred first method, but depending on the size and shape of the wood molding, the type of curable resin, etc., it is possible to manufacture the wood molding by appropriately setting not only the press schedule but also other molding conditions.

[0038] In the first method, when the hardening resin is a thermosetting resin, it is necessary to heat the mold to a temperature at which the resin can be hardened. The heating start time may be any of the following: before the start of compression, between the compression start time t1 and the compression end time t2 (while the load application process is being performed), and between the start of unloading (the compression end time t2) and the unloading end time t3 (while the unloading process is being performed). When heating to a hardening temperature is performed between the start of unloading (the compression end time t2) and the unloading end time t3, the mold may be preheated between the start of compression and the compression end time t2. When the hardening resin is a thermosetting resin, it is preferable to perform the load application process and the unloading process under heating conditions. As described above, when the shape of the woody molded body to be manufactured is not simple and requires compression from multiple directions, for example, the load application process and the unloading process are repeated, the load application process and the unloading process in the last cycle may be under heating conditions, for example.

[0039] In the press schedule of Figure 3, the holding time Δt1 in the compressed state and the unloading time Δt2 are selected appropriately depending on the size and shape of the wood molding, the type of curable resin, the impregnation ratio of the curable resin to the wood raw material, whether or not the mold is heated, the structure and shape of the mold, etc.

[0040] When the curable resin is a thermosetting resin and heating of the mold to a temperature at which the resin can be cured is started before compression begins, a wood molded product having a porosity originating from the wood cell cavities of 5 to 60% and a feel similar to that of wood can be efficiently obtained. Therefore, the holding time Δt1 is preferably 0.3 to 60 seconds, more preferably 0.4 to 20 seconds, even more preferably 0.5 to 5 seconds, and particularly preferably 0.5 to 3 seconds, and the unloading time Δt2 is preferably 0.2 to 30 seconds, more preferably 0.3 to 10 seconds, even more preferably 0.4 to 5 seconds, and particularly preferably 0.5 to 3 seconds. In addition, the retention time from the end time t3 of unloading is not particularly limited, but is preferably 120 to 1800 seconds from the viewpoints of shape retention, reaction rate of the curable resin, generation of compounds accompanying the curing reaction, thermal decomposition of the wood material, etc.

[0041] Figure 4 shows an example of a pressing schedule after the load application step in the second method, that is, a pressing schedule in which a molding machine equipped with a mold having a cavity that reflects the shape of a wood molded body is used, and a load application step is performed once to place a resin-impregnated material in the cavity of the mold and apply a load to obtain a precursor molded body of a smaller size than the shape formed by the resin-impregnated material in at least one direction, which is smaller than the shape formed by the resin-impregnated material, relative to the desired wood molded body, and then an unloading step is performed to unload the unhardened wood molded body (M2) until it is larger than the final product, and a resin hardening step is performed to harden the hardenable resin contained in the unhardened wood molded body (M2), thereby producing a wood molded body of the desired size and shape.

[0042] The pressing schedule of FIG. 4 applies a load to the resin-impregnated material in the die until the desired wood body is smaller than the size of the desired wood body, i.e., the punch stroke S a For example, the compressed state with the maximum pressure (compression start time t1) is held for a certain time (holding time Δt1) until the precursor compact is formed (compression end time t2), and then the punch stroke S is set to a state where the internal structure of the die has a desired shape and size. bThe load applied to the precursor compact is reduced and unloading is performed to make the size larger than the final product (unloading time Δt2) until the unloading end time t3 is reached. b This state is maintained for a certain period of time (end of holding time t4), after which a load according to the desired size is applied (end of compression time t5), and then maintained to completely harden the hardenable resin and obtain a wood molded body containing the wood material and the hardened resin.

[0043] In the second method, it is preferable to set the pressing schedule so that the hardening of the hardening resin starts at or after the retention end time t4. It is also preferable to set the softening of the hardening resin and the cell walls impregnated with the hardening resin starts at or before the compression start time t1. It is necessary to soften and deform at least by the compression end time t2.

[0044] The press schedule in Figure 4 shows the relationship between molding time and punch stroke for carrying out the preferred second method, but as with the press schedule in Figure 3 for the first method, the wood molded body can be produced by appropriately setting not only the press schedule but also other molding conditions depending on the size and shape of the wood molded body, the type of curable resin, etc.

[0045] In the second method, when the curable resin is a thermosetting resin, the load application step and the unloading step according to the first method can be applied as they are. When the start of heating the mold to a temperature at which the resin can be cured is set before the start of the first compression, the holding time in the compressed state (first compression holding time) Δt1 is preferably 0.3 to 90 seconds, more preferably 0.4 to 60 seconds, even more preferably 0.5 to 40 seconds, and particularly preferably 0.5 to 30 seconds, and the unloading time Δt2 is preferably 0.2 to 90 seconds, more preferably 0.3 to 60 seconds, even more preferably 0.4 to 30 seconds, and particularly preferably 0.5 to 15 seconds. In the second method, since a wood molding having a porosity originating from wood cell cavities of 5 to 60% and excellent wood appearance and gloss can be efficiently obtained, the holding time Δt3 of the unloaded state from the end time t3 of unloading is preferably 1 to 90 seconds, more preferably 3 to 60 seconds, and even more preferably 10 to 60 seconds, and the holding time (second compressed holding time) Δt4 in the compressed state in which the load is reapplied after unloading is not particularly limited, but is preferably 120 to 1800 seconds from the viewpoints of shape retention, reaction rate of the curable resin, generation of compounds accompanying the curing reaction, thermal decomposition of the wood material, etc.

[0046] The woody molded product obtained by the method for producing a woody molded product of the present invention has an excellent woody appearance on at least one surface or on the entire surface. In addition, the woody molded product may have an excellent gloss. Furthermore, the density of the obtained woody molded product is preferably 0.5 to 1.3 g / cm. 3 , more preferably 0.6 to 1.1 g / cm 3 The density of wood varies greatly depending on the type of wood, the growth conditions, the location of cutting, and even within a single tree, and is in the range of 0.2 to 1.2 g / cm 3 (The density of coniferous trees such as cedar, cypress, and pine is usually 0.4 to 0.6 g / cm 3 ), the density of the woody molding of the present invention is the same or up to three times higher, but still has a texture that is sufficiently close to that of wood.

[0047] The wood molded body manufacturing method of the present invention can be used to manufacture a composite body (three-dimensional molded body) consisting of a part made of a wood molded body having a feel similar to wood (hereinafter referred to as the "wood molded body part") and an adherend part joined to this wood molded body part (see Figure 35).

[0048] Fig. 35 is an explanatory diagram for producing a composite 51 in which an adherend portion 42 derived from the prepreg 41 and a woody molded body portion 47 derived from the resin-impregnated material 45 are joined using a prepreg 41 made of a woody molded body as an adherend and a resin-impregnated material 45. The resin-impregnated material 45 is a raw material that gives a woody molded body portion 47 having a texture similar to that of wood, and the surface of the woody molded body portion 47 of the composite 51 thus formed has the shape shown in Fig. 36. On the other hand, the prepreg 41 that becomes the adherend portion 42 undergoes no or only slight change in shape even in the resulting composite 51, and in the composite 51, the surface of the adherend portion 42, which is the bottom surface of the prepreg 41, has the shape shown in Fig. 37.

[0049] In the following explanation using Figure 35, we will use a prepreg 41 containing a wood material and a cured resin, and a resin-impregnated material 45 obtained by impregnating a wood raw material with a thermosetting resin, and we will assume that the size and shape of the prepreg 41 do not change at the curing temperature of the thermosetting resin. FIG. 35(I) shows a scene in which the prepreg 41 from which the composite 51 is finally formed and which becomes the adherend portion 42 is placed on the lower die 33 in the mold 31. 35(II) shows a scene in which a resin-impregnated material 45 is loaded onto the prepreg 41. In this figure, one resin-impregnated material 45 is used, but a plurality of small-sized resin-impregnated materials 45 may be used. 35(III) shows a scene in which the mold 31 is in a heated state and the resin-impregnated material 45 is compressed by the upper mold 35, for example, with the maximum pressure stroke, so that a precursor portion 46 having a thickness smaller than the desired size is in close contact with the upper surface of the prepreg 41. In this close contact state, the mold 31 is heated, but the thermosetting resin contained in the precursor portion 46 is not completely cured. Figure 35 (IV) shows a scene in which the precursor portion 46 of Figure 35 (III) is preferably brought into contact with the inner surface of upper mold 35 while being unloaded by upper mold 35, i.e., upper mold 35 is moved until the thickness of precursor portion 46 becomes the thickness of wood molded body portion 47, and then upper mold 35 is fixed and the thermosetting resin is completely cured to obtain a composite 51 in which wood molded body portion 47 is bonded to the upper surface of prepreg 41 (adherend portion 41).

[0050] The wood molded body portion of the wood molded body or composite of the present invention has a feel similar to that of wood, and therefore is suitable for use in everyday items, furniture, building materials, construction components, electrical appliances or audio equipment housings, vehicle components (interior materials, etc.), etc., taking advantage of this property. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" are by weight unless otherwise specified.

[0052] 1. Manufacturing and evaluation of wood-based moldings (1) In the following Example 1 and Comparative Examples 1 and 2, a 4 mm thick (R: radial direction) Hinoki veneer (with density ρ a :0.47g / cm 3 ) was impregnated with an aqueous solution of thermosetting phenolic resin with a solid content concentration of 30%, dried at 35°C, and cut into a disk shape with a diameter of about 52 mm to obtain a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X1)"). The content of the phenolic resin (solid content) in this resin-impregnated material (X1) was 46%, the weight increase rate due to the impregnated phenolic resin was 85%, and the density was about 0.64 g / cm 3 It is. In addition, a mold having a cylindrical cavity with an inner diameter of 53 mm was used to manufacture the wood molded body.

[0053] Example 1 Based on the pressing schedule shown in FIG. 5, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (C1)") was manufactured. First, four pieces of resin-impregnated material (X1) (total thickness: about 16 mm, diameter: about 52 mm, total mass: about 25 grams) were stacked and placed in a mold. Then, the mold was heated so that the temperature of the inner surface of the mold was 155°C, and a mirror-finished flat punch was used to press from above with a load of 10 tons (punch surface pressure: 47 MPa), and this state was maintained for 5 seconds. At this time, the punch stroke (Sa) was about 9 mm. After that, while maintaining the contact state of the resin-impregnated material (X1) with the surface of the punch that was in contact with the resin-impregnated material (X1), the load was removed by about 2 mm, and the position of the punch was maintained. Note that the mold temperature was maintained at the same 155°C as above until 120 seconds had elapsed from the start of unloading, and until a total of about 415 seconds had elapsed after 120 seconds had elapsed, the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold to cool the molded product. The mold was then removed to obtain a disk-shaped woody molding (C1) containing a wood material made of cypress and a phenol-hardened resin, with the desired diameter of 53 mm and thickness of about 9.5 mm. The woody texture of the obtained woody molding (C1) was evaluated by touching the surface, which was found to be good. Figure 6 shows an image obtained by photographing one surface of the woody molding (C1) with a camera.

[0054] The woody molded body (C1) was cut perpendicularly (in the thickness direction of the molded body) to the wood cells extending in the longitudinal direction, and the exposed cross section (end grain cross section) was polished. Then, images of two regions at different depths from the surface toward the inside were obtained using a digital microscope "VHX-970F" (model name) manufactured by Keyence Corporation. FIG. 7 is an image of the end grain cross section at a depth of about 0.5 mm from the surface of the woody molded body (C1), and FIG. 9 is an image of the end grain cross section at a depth of about 3 mm from the surface of the woody molded body (C1). It can be seen from FIGS. 7 and 9 that the woody cells have a portion that is arranged in a curved shape rather than in a regular arrangement. Also, FIG. 11 is an image (enlarged image) of the end grain cross section at a depth of about 3 mm from the surface of the woody molded body (C1), and it can be seen from FIG. 11 that the woody cells are deformed due to shear deformation or buckling of the cell wall. In addition, in Figs. 7 and 9, the colorless (white) parts are phenol-cured resin, but in order to distinguish the voids originating from the wood cell lumen, binarized images were obtained by dividing the wood cells containing phenol-cured resin and the voids originating from the wood cell lumen based on the difference in brightness of these microscopic images. Fig. 8 is the binarized image of Fig. 7, and Fig. 10 is the binarized image of Fig. 9. In Figs. 8 and 10, the colorless (white) parts are the voids originating from the wood cell lumen, so the ratio of the total area of ​​the voids to the total area of ​​each image (porosity) was calculated. The experiment to calculate the porosity was performed on five image samples of the woody molding (C1), and the results (average values) are shown in Table 1.

[0055] The density of the woody molded body (C1) was calculated from its mass and volume and is shown in Table 1. Furthermore, the color difference ΔE between one surface of the wood molding (C1) shown in Figure 6 and the raw material, cypress veneer, was calculated using the SCE (specular reflection elimination) method using a Konica Minolta spectrophotometer “CM-3610d” (model name), and is shown in Table 1.

[0056] Comparative Example 1 Based on the pressing schedule shown in FIG. 12, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (C2)") was manufactured. As in Example 1, first, four sheets of resin-impregnated material (X1) were stacked and placed in a mold. Then, the mold was heated so that the temperature of the inner surface of the mold was 155°C, and a mirror-finished flat punch was used to apply a load from above until the distance from the bottom surface of the mold cavity to the punch in contact with the material was about 9.5 mm, and the punch was held at that position for 120 seconds. From the time 120 seconds had passed until a total of about 420 seconds had passed, the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold to cool the molded product. After that, the mold was demolded to obtain a disk-shaped wood molded product (C2) having the desired diameter of 53 mm and thickness of about 9.5 mm, which contained a wood material made of cypress and a phenol-hardened resin. When the surface of the obtained wood molded product (C2) was touched and its feel was evaluated, the wood texture was not felt sufficiently and the feel was poor. FIG. 13 is an image obtained by photographing one surface of this woody molded product (C2) with a camera.

[0057] The woody molded body (C2) was cut in a direction perpendicular to the longitudinally extending wood cells (thickness direction of the molded body) in the same manner as the woody molded body (C1) of Example 1, and the exposed cross section (end grain cross section) was polished. Then, images of two regions at different depths from the surface toward the inside were obtained using the digital microscope. FIG. 14 is an image of the end grain cross section at a depth of about 0.5 mm from the surface of the woody molded body (C2), and FIG. 15 is an image of the end grain cross section at a depth of about 3 mm from the surface of the woody molded body (C2). FIG. 15 shows that the woody cells are regularly arranged. FIG. 16 is an image (enlarged image) of the end grain cross section at a depth of about 3 mm from the surface of the woody molded body (C2), and FIG. 16 shows that no deformation of the woody cells is observed.

[0058] Moreover, in the same manner as for the wood molded body (C1) of Example 1, the binarized image of FIG. 14 (not shown) and the binarized image of FIG. 17 (not shown) were created, and the ratio of the total area of ​​the voids originating from the wood cell lumen to the total area of ​​each image (porosity) was calculated. The experiment to calculate the porosity was performed on five image samples, as described above. Furthermore, in the same manner as for the wood molded body (C1) of Example 1, the density and color difference ΔE of the wood molded body (C2) were measured. The results are shown in Table 1.

[0059] Comparative Example 2 Based on the pressing schedule shown in FIG. 17, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (C3)") was manufactured. As in Example 1, first, four sheets of resin-impregnated material (X1) were stacked and placed in a mold. Then, the mold was heated so that the temperature of the inner surface of the mold was 150°C, and a mirror-finished flat punch was used to press from above with a load of 10 tons (punch surface pressure: 47 MPa), and this state was maintained for 420 seconds. At this time, the punch stroke (Sa) was about 9 mm. After that, the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold to cool the molded product. Then, the mold was demolded to obtain a disk-shaped wood molded product (C3) containing a wood material made of cypress and a phenol-hardened resin, with a diameter of 53 mm and a thickness of about 7.3 mm. When the surface of the obtained wood molded product (C3) was touched and its feel was evaluated, the wood texture was not felt sufficiently, and the feel was poor. In addition, if the load of about 2 mm as in Example 1 was not removed, the molded product became smaller than the desired thickness (about 9.5 mm). FIG. 18 is an image obtained by photographing one surface of this woody molded product (C3) with a camera.

[0060] The woody molded body (C3) was cut in a direction perpendicular to the longitudinally extending wood cells (thickness direction of the molded body) in the same manner as the woody molded body (C1) of Example 1, and the exposed cross section (end section) was polished. Then, using the digital microscope, images of two regions at different depths from the surface toward the inside were obtained (not shown), that is, an end section image at a depth of about 0.5 mm from the surface of the woody molded body (C3) and an end section image at a depth of about 3 mm from the surface of the woody molded body (C3). Then, a binarized image was created only for the former image, and the ratio of the total area of ​​the voids derived from the woody cell lumen to the total area (porosity) was calculated. The experiment to calculate the porosity was performed on five image samples in the same manner as above. Furthermore, the density and color difference ΔE of the woody molded body (C3) were measured in the same manner as the woody molded body (C1) of Example 1. The results are shown in Table 1.

[0061] [Table 1]

[0062] In the woody molded body (C1) obtained in Example 1, the porosity in the interior (two locations) at different depths from the surface was about 45% in both cases. The porosity in the shallow regions in Comparative Examples 1 and 2 was 1-15%, while the porosity in the deep region in Comparative Example 1 was about 45%. The porosity in the shallow region in Example 1 was larger than those in Comparative Examples 1 and 2. Furthermore, the difference in porosity between the two locations was about 31 points in Comparative Example 1, but was small at 2.2 points in Example 1. Furthermore, when the woody molded body (C1) was touched with the hand, it felt similar to wood. The obtained woody molded product (C1) had a smaller color difference ΔE than the woody molded products (C2) and (C3) obtained in Comparative Examples 1 and 2, and a wood-like grain was confirmed.

[0063] 2. Manufacturing and evaluation of wood-based moldings (2) In the following Examples 2 to 4 and Comparative Example 3, a cypress veneer having a thickness of 4 mm (R: radial direction) (density ρ a :0.47g / cm3 ) was impregnated with an aqueous solution of thermosetting phenolic resin with a solid content concentration of 30%, dried at 35°C, and then cut into a piece of 10 mm (L: fiber direction) x 10 mm (T: tangential direction) to obtain a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X2)"). The content of the phenolic resin (solid content) in this resin-impregnated material (X2) was 46%, and the density was approximately 0.64 g / cm 3 It is. Moreover, to manufacture the woody molded body, the same mold as in Example 1, having a cylindrical cavity with an inner diameter of 53 mm, was used.

[0064] Example 2 Based on the pressing schedule shown in FIG. 5, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (D1)") was manufactured. First, a dozen or so pieces of the resin-impregnated material (X2) (total mass: 10 grams) were placed in a mold in a state of high filling rate (thickness of the resin-impregnated material in the mold: about 10 mm). Then, the mold was heated so that the temperature of the inner surface of the mold was 150°C, and a mirror-finished flat punch was used to press from above with a load of 60 tons (punch surface pressure: 272 MPa), and this state was maintained for 5 seconds. At this time, the punch stroke (Sa) was about 6 mm. After that, while maintaining the contact state of the resin-impregnated material (X2) with the surface of the punch that was in contact with the resin-impregnated material (X2), about 2.1 mm of the load was removed, and the position of the punch was maintained. Note that the mold temperature was maintained at the same 150°C as above until 120 seconds had elapsed from the start of the unloading, and until a total of about 415 seconds had elapsed after 120 seconds had elapsed, the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold to cool the molded product. After that, the mold was removed to obtain a disk-shaped woody molded product (D1) containing a wood material made of cypress and a phenol-hardened resin and having the desired diameter of 53 mm and thickness of 4.44 mm. Figure 19 shows an image obtained by photographing one surface of this woody molded product (D1) with a camera.

[0065] The obtained woody molded body (D1) was cut and processed, and the exposed cross section (end grain cross section) cut perpendicular to the longitudinally extending wood cells was polished. Then, using the digital microscope, images of two regions at different depths from the surface toward the inside were obtained. An image of an end grain cross section at a depth of about 0.5 mm from the surface of the woody molded body (D1) is shown in FIG. 20. In order to evaluate the wood texture of the obtained woody molded body (C1), the surface was touched and the feel was evaluated, which was found to be good. FIG. 20 shows that the woody molded body contains deformed woody cells, and furthermore, there is evidence of a change in the positional relationship between adjacent woody cells, indicating the occurrence of plastic flow due to intercellular slippage.

[0066] As with the woody molding (C1) of Example 1, the binary image of FIG. 20 (not shown) and a binary image of a cross-sectional image of wood cells at a depth of about 0.5 mm from the surface of the woody molding (D1), not shown, were created, and the ratio of the total area of ​​voids originating from the woody cell lumen to the total area of ​​each image (porosity) was calculated. The experiment to calculate the porosity was performed on five image samples, as described above. Furthermore, the density and color difference ΔE of the woody molding (D1) were measured in the same manner as with the woody molding (C1) of Example 1. The results and texture are shown in Table 2.

[0067] Example 3 After applying a load to the resin-impregnated material (X2) in the mold, the resin-impregnated material (X2) was unloaded by about 1.0 mm while maintaining the contact state of the resin-impregnated material (X2) with the surface of the punch that had been in contact with the material. The same operations as in Example 2 were performed to obtain a disk-shaped woody molding (D2) with the desired diameter of 53 mm and thickness of 3.38 mm. The difference between the unloading of 2.1 mm in Example 2 and the unloading of 1 mm in this example resulted in a woody molding with a difference of about 1.1 mm in thickness. In order to evaluate the wood texture of the obtained woody molding (D2), the surface was touched and the tactile sensation was evaluated, and the tactile sensation was good. Figure 21 is an image obtained by photographing one side surface of this woody molding (D2) with a camera. The obtained wood molding (D2) was subjected to the same operations as in Example 2 to measure the porosity at a depth of about 0.5 mm from the surface of the wood molding (D2), the porosity at a depth of about 1.5 mm from the surface of the wood molding (D2), the density, and the color difference ΔE. The results are shown in Table 2.

[0068] Example 4 After applying a load to the resin-impregnated material (X2) in the mold, the resin-impregnated material (X2) was maintained in contact with the surface of the punch, and the load was removed by about 0.3 mm. The same operations as in Example 2 were performed to obtain a disk-shaped woody molding (D3) with the desired diameter of 53 mm and thickness of 2.65 mm. In order to evaluate the wood texture of the obtained woody molding (D3), the surface was touched and the tactile sensation was evaluated, and the tactile sensation was good. Figure 22 is an image obtained by photographing one side surface of this woody molding (D3) with a camera. The obtained wood molding (D3) was subjected to the same operations as in Example 2 to measure the porosity at a depth of about 0.5 mm from the surface of the wood molding (D3), the porosity at a depth of about 1.5 mm from the surface of the wood molding (D3), density, and color difference ΔE. The results are shown in Table 2.

[0069] Comparative Example 3 Based on the pressing schedule shown in FIG. 17, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (D4)") was manufactured. As in Example 2, first, a dozen or so pieces of the resin-impregnated material (X2) (total mass: 10 grams) were placed in a mold in a state of high filling rate. Then, the mold was heated so that the temperature of the inner surface of the mold was 155°C, and a mirror-finished flat punch was used to apply a load of 10 tons (punch surface pressure: 47 MPa) from above until the distance from the bottom surface of the cavity of the mold to the punch in contact with the material was about 2.3 mm, and the punch was held at that position for 420 seconds. After that, the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold to cool the molded product. Then, the mold was demolded to obtain a disk-shaped wood molded product (D4) with a diameter of 53 mm and a thickness of 2.33 mm, which contained a wood material made of cypress and a phenol-cured resin. The surface of the obtained wood molded product (D4) was evaluated for its feel, and the feel was poor, with no sense of woodiness being felt sufficiently. FIG. 23 is an image obtained by photographing one surface of this woody molded product (D4) with a camera.

[0070] The obtained woody molded body (D4) was cut and processed, and the exposed cross section (end grain cross section) cut perpendicular to the longitudinally extending wood cells was polished, after which images of two regions at different depths from the surface toward the inside were obtained using the digital microscope. An image of the inside, about 0.5 mm deep from the surface of the woody molded body (D1), is shown in Figure 24. Figure 24 shows that almost all of the cells have been deformed, and there are almost no voids originating from the intracellular cavities.

[0071] 24 (not shown) was created, and the ratio of the total area of ​​voids originating from wood cell cavities to the total area of ​​the image (porosity) was calculated. The density and color difference ΔE of the woody molded body (D4) were measured in the same manner as for the woody molded body (C1) of Example 1. The results and texture are shown in Table 2.

[0072] [Table 2]

[0073] In the woody molded bodies obtained in Examples 2 to 4, the porosity at two different depths from the surface was greater than that of Comparative Example 3, and the difference in porosity at the two locations was 15 points or less. When the woody molded bodies (D1) to (D3) were touched with the hand, they had a texture similar to that of wood. The densities of the woody molded products (D1) to (D3) obtained in Examples 2 to 4 were greater than that of the raw material resin-impregnated material (X2) but smaller than that of the woody molded product (D4) obtained in Comparative Example 3. The obtained woody molded products (D1) to (D3) had a smaller color difference ΔE than the woody molded product (D4) obtained in Comparative Example 3, and more wood-like grain was observed than in Comparative Example 3.

[0074] It was found from Examples 1 to 4 above that the difference in porosity between the shallow region from the surface and the deeper region within the woody molded product could be made 15 percentage points or less.

[0075] 3. Manufacturing and evaluation of wood-based moldings (3) In the following Examples 5 to 7 and Comparative Example 4, a 4 mm thick (R: radial direction) Hinoki veneer (with density ρ a :0.47g / cm 3 ) was impregnated with an aqueous thermosetting melamine resin solution with a solid content concentration of 30%, dried at 35°C, and then cut into a piece of 10 mm (L: fiber direction) x 10 mm (T: tangential direction) to obtain a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X3)"). In this resin-impregnated material (X3), the content of the melamine resin (solid content) was 38 to 41%, the moisture content was 0%, and the density was approximately 0.64 g / cm 3 It is. Moreover, to manufacture the woody molded body, the same mold as in Example 1, having a cylindrical cavity with an inner diameter of 53 mm, was used.

[0076] Example 5 Based on the pressing schedule shown in FIG. 5, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (E1)") was manufactured. First, a dozen or so pieces of the resin-impregnated material (X3) (total mass: 10 grams) were placed in a mold in a state of high filling rate (thickness of the resin-impregnated material in the mold: about 10 mm). Then, the mold was heated so that the temperature of the inner surface of the mold was 170°C, and a mirror-finished flat punch was used to press from above with a load of 60 tons (punch surface pressure: 272 MPa), and this state was maintained for 5 seconds. At this time, the punch stroke (Sa) was about 3.5 mm. Then, while maintaining the contact state of the resin-impregnated material (X3) with the surface of the punch that was in contact with the resin-impregnated material (X3), the load was removed by about 0.4 mm, and the position of the punch was maintained. Incidentally, even after the load was removed, the mold temperature was kept at the same 170°C as above, and after 420 seconds had passed, the mold was demolded to obtain a disk-shaped woody molding (E1) having the desired diameter of 53 mm and thickness of 3.88 mm, which contained a woody material made of cypress and a melamine-cured resin. FIG. 25 is an image obtained by photographing one surface of this woody molded product (E1) with a camera.

[0077] The obtained woody molded body (E1) was cut and processed, and the exposed cross section (end grain cross section) cut perpendicular to the longitudinally extending wood cells was polished, and then an image of the inside of the woody molded body (E1) at a depth of about 0.5 mm from the surface was obtained using the digital microscope. Then, as with the woody molded body (C1) of Example 1, this image was binarized, and the ratio of the total area of ​​the voids originating from the woody cell lumen (porosity) was calculated from the obtained image. The results and texture are shown in Table 3.

[0078] Example 6 Except for changing the unloading amount to about 0.1 mm, the same operation as in Example 5 was carried out to obtain a disk-shaped woody molding (E2) containing a wood material made of cypress and melamine-cured resin and having the desired diameter of 53 mm and thickness of 3.56 mm. Figure 26 is an image obtained by photographing one surface of this woody molding (E2) with a camera.

[0079] The obtained woody molded body (E2) was cut and processed, and the exposed cross section (end grain cross section) cut perpendicular to the longitudinally extending wood cells was polished, and then an image of the end grain cross section at a depth of about 0.5 mm from the surface of the woody molded body (C2) was obtained using the digital microscope (see FIG. 27). Then, as with the woody molded body (C1) of Example 1, a binarized image (not shown) of FIG. 27 was created, and the ratio of the total area of ​​voids originating from the woody cell lumen to the total area of ​​the image (porosity) was calculated. These results and tactile sensations are shown in Table 3.

[0080] Example 7 Except for changing the unloading amount to about 0.2 mm, the same operation as in Example 5 was carried out to obtain a disk-shaped woody molding (E3) containing a wood material made of cypress and melamine-cured resin and having the desired diameter of 53 mm and thickness of 3.60 mm. Figure 28 is an image obtained by photographing one surface of this woody molding (E3) with a camera. Thereafter, the porosity was measured in the same manner as in Example 5, and the results and the feel are shown in Table 3.

[0081] Comparative Example 4 Based on the pressing schedule shown in FIG. 17, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (E4)") was manufactured. As in Example 5, a dozen or so pieces of the resin-impregnated material (X3) (total mass: 10 grams) were placed in a mold in a state of high filling rate. Then, the mold was heated so that the temperature of the inner surface of the mold was 170°C, and a mirror-finished flat punch was used to press from above under a load of 60 tons until the distance from the bottom of the cavity of the mold to the punch that contacted the material was about 3.5 mm, and the punch was held in that position for 420 seconds. After that, the mold was removed to obtain a disk-shaped woody molded body (E4) with a diameter of 53 mm and a thickness of 3.45 mm, which contains a woody material made of cypress and a melamine-cured resin. Figure 29 is an image obtained by photographing one side surface of this woody molded body (E4) with a camera. Thereafter, the porosity was measured in the same manner as in Example 5, and the results and the feel are shown in Table 3.

[0082] Next, in the following Examples 8 to 10 and Comparative Example 5, a 4 mm thick (R: radial direction) Hinoki veneer (with density ρ a :0.47g / cm 3 ) was impregnated with a thermosetting melamine resin aqueous solution with a solid content of 30%, dried at 35°C, cut into pieces of 10 mm (L: fiber direction) x 10 mm (T: tangential direction), and further sprayed with water to adjust the moisture content to 5% to prepare a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X4)"). The content of the melamine resin in this resin-impregnated material (X4) is 38 to 41%. Moreover, to manufacture the woody molded body, the same mold as in Example 1, having a cylindrical cavity with an inner diameter of 53 mm, was used.

[0083] Example 8 Except for using a resin-impregnated material (X4) of almost the same shape instead of the resin-impregnated material (X3) and changing the unloading amount to about 1.3 mm, the same operation as in Example 5 was carried out to obtain a disk-shaped woody molding (F1) containing a woody material made of cypress and melamine-cured resin and having the desired diameter of 53 mm and thickness of 4.54 mm. Figure 30 is an image obtained by photographing one surface of this woody molding (F1) with a camera.

[0084] Next, similarly to the woody molding (E1) of Example 5, images were taken of the interior of the woody molding (F1) at a depth of about 0.5 mm from the surface, and the porosity was measured. The results and the feel are shown in Table 3.

[0085] Example 9 Except for using a resin-impregnated material (X4) of almost the same shape instead of the resin-impregnated material (X3) and changing the unloading amount to about 0.6 mm, the same operation as in Example 6 was carried out to obtain a disk-shaped woody molding (F2) with a diameter of 53 mm and a thickness of 3.83 mm, which contains a woody material made of cypress and melamine-cured resin. Figure 31 is an image obtained by photographing one surface of this woody molding (F2) with a camera.

[0086] Next, similarly to the woody molding (E1) of Example 5, images were taken of the interior of the woody molding (F2) at a depth of about 0.5 mm from the surface, and the porosity was measured. The results and the feel are shown in Table 3.

[0087] Example 10 Except for using a resin-impregnated material (X4) of almost the same shape instead of the resin-impregnated material (X3) and changing the unloading amount to about 0.4 mm, the same operation as in Example 7 was carried out to obtain a disk-shaped woody molding (F3) containing a woody material made of cypress and melamine-cured resin and having the desired diameter of 53 mm and thickness of 3.63 mm. Figure 32 is an image obtained by photographing one surface of this woody molding (F3) with a camera.

[0088] Next, similarly to the woody molding (E1) of Example 5, images were taken of the interior of the woody molding (F3) at a depth of about 0.5 mm from the surface, and the porosity was measured. The results and the feel are shown in Table 3.

[0089] Comparative Example 5 Except for using resin-impregnated material (X4) of almost the same shape instead of resin-impregnated material (X3), the same operation as in Comparative Example 4 was carried out to obtain a disk-shaped woody molding (F4) of 53 mm in diameter and 3.23 mm in thickness, which contained a woody material made of cypress and melamine-cured resin. Figure 33 is an image obtained by photographing one surface of this woody molding (F4) with a camera.

[0090] Next, similarly to the woody molding (E4) of Comparative Example 4, images were taken of the interior of the woody molding (F4) at a depth of about 0.5 mm from the surface, and the porosity was measured. The results and the feel are shown in Table 3.

[0091] [Table 3]

[0092] 4. Manufacturing and evaluation of wood-based moldings (4) In the following Examples 11 and 12 and Comparative Example 6, a 4 mm thick (R: radial direction) Hinoki veneer (density ρa :0.47g / cm 3 ) was impregnated with an aqueous solution of thermosetting melamine resin with a solid content concentration of 10%, dried at 35°C, and cut into a disk shape with a diameter of about 52 mm to obtain a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X5)"). The content of the melamine resin (solid content) in this resin-impregnated material (X5) was 17 to 23%, and the density was about 0.48 g / cm 3 It is. Moreover, to manufacture the woody molded body, the same mold as in Example 1, having a cylindrical cavity with an inner diameter of 53 mm, was used.

[0093] Example 11 Based on the pressing schedule shown in FIG. 5, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (G1)") was manufactured. First, three pieces of resin-impregnated material (X5) (total thickness: about 12 mm, diameter: about 52 mm, total mass: about 10 grams) were stacked and placed in a mold. Then, the mold was heated so that the temperature of the inner surface of the mold was 170°C, and a mirror-finished flat punch was used to press from above with a load of 10 tons (punch surface pressure: 45 MPa) for one second. At this time, the punch stroke (Sa) was about 8.7 mm. Then, while maintaining the contact state of the resin-impregnated material (X5) with the surface of the punch that was in contact with the resin-impregnated material (X5), the load was removed by about 0.5 mm, and the position of the punch was held for 420 seconds. Next, the mold was demolded without supplying cooling water to the mold, and a disk-shaped wood molded body (G1) containing a wood material made of cypress and a melamine-cured resin and having a desired diameter of 53 mm and a thickness of about 3.8 mm was obtained. In order to evaluate the woody texture of the obtained wood molded product (G1), the surface was touched and the feel was evaluated, which was found to be good.

[0094] The arithmetic mean roughness Ra and maximum height Rz of the circular surface of the obtained wood molding (G1) were measured at a temperature of 20°C using a Tokyo Seimitsu stylus-type roughness tester "SURFCOM 1800G-13" (model name) with a measurement length of 4 mm. In addition, the wood molding (G1) was conditioned for 7 days in an environment with a temperature of 20°C and a relative humidity of 60%, and then the thermal conductivity at a temperature of 20°C was measured using a Kyoto Electronics Manufacturing Co., Ltd. rapid thermal conductivity meter "QTM-500" (model name), and the Brinell hardness was measured using a Shimadzu Corporation small tabletop testing machine "EZ-TEST EZ-S" (model name). These results, along with the density and color difference ΔE of the wood molding (G1), are shown in Table 4. The thermal conductivity of the above-mentioned cypress veneer is 0.132 W / (m K), and the Brinell hardness is 10.8.

[0095] Example 12 In Example 11, the same operation as in Example 11 was carried out, except that the unloading amount for the resin-impregnated material (X5) pressed in the mold was changed to about 0.3 mm, to obtain a disk-shaped woody molding (G2) with a thickness of about 3.6 mm. Various evaluations were then carried out. The results are shown in Table 4.

[0096] Comparative Example 6 Based on the pressing schedule shown in FIG. 17, a disk-shaped wood molded product (hereinafter referred to as "wood molded product (G3)") was manufactured. First, three pieces of resin-impregnated material (X5) (total mass: about 10 grams) were stacked and placed in a mold. The mold was then heated so that the temperature of the inner surface of the mold reached 170°C, and pressed from above with a load of 10 tons (punch surface pressure: 45 MPa) for 420 seconds. The mold was then demolded without supplying cooling water to obtain a disk-shaped wood molded body (G3) with a diameter of 53 mm and a thickness of about 3.3 mm, which contained a wood material made of cypress and melamine-cured resin. Various evaluations were then carried out. The results are shown in Table 4.

[0097] [Table 4]

[0098] The densities of the disc-shaped wood moldings (G1) and (G2) obtained in Examples 11 and 12 were greater than the density of the raw material resin-impregnated material (X5), but less than the density of the disc-shaped wood molding (G3) obtained in Comparative Example 6. The obtained disc-shaped wood moldings (G1) and (G2) had a smaller color difference ΔE than the disc-shaped wood molding (G3) obtained in Comparative Example 6, and had a wood-like grain compared to Comparative Example 6, and also had a good feel. In addition, the Brinell hardness of the obtained disc-shaped wood moldings (G1) and (G2) was closer to the Brinell hardness of cypress veneer (10.8) than that of Comparative Example 6. This Brinell hardness is considered to be one of the physical properties that affect the wood texture.

[0099] 5. Manufacturing and evaluation of wood-based moldings (5) In the following Examples 13 and 14 and Comparative Example 7, a hinoki veneer having a thickness of 4 mm (R: radial direction) (density ρ a :0.47g / cm 3 ) was impregnated with an aqueous solution of thermosetting melamine resin with a solid content concentration of 30%, dried at 35°C, and cut into a disk shape with a diameter of about 52 mm to obtain a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X6)"). The content of the melamine resin (solid content) in this resin-impregnated material (X6) was 38 to 41%, and the density was about 0.64 g / cm 3 It is.

[0100] Example 13 The same procedure as in Example 11 was carried out except that the resin-impregnated material (X5) was replaced with the resin-impregnated material (X6) with a total mass of about 15 grams, the punch stroke (Sa) was set to about 7.4 mm, and the unloading amount was set to about 1.5 mm, to obtain a disk-shaped woody molding (H1) with a diameter of 53 mm and a thickness of about 6.0 mm (see FIG. 34). Thereafter, the density, color difference, surface roughness, thermal conductivity, and Brinell hardness were measured, and the results are shown in Table 5.

[0101] Further, detailed tactile evaluation of the obtained woody moldings was performed by the following method. Specifically, six adults served as sensory evaluators (T1) to (T6), and judged the woody moldings by touching them with and without blindfolding in three categories: (I) wood-likeness (woody texture), (II) warmth, and (III) softness, according to the following criteria. The results are shown in Table 6. (I) Wood texture 1: Very good 2: Good 3: Poor 4: Similar to plastic products (II) Warmth 1: Very warm 2: Warm 3: Cold 4: Very cold (III) Softness 1: Very soft 2: Soft 3: Hard 4: Very hard

[0102] Example 14 The same operations as in Example 11 were carried out except that the resin-impregnated material (X5) was replaced with a resin-impregnated material (X6) with a total mass of about 15 grams, the punch stroke (Sa) was set to about 7.4 mm, and the unloading amount was set to about 1.0 mm, to obtain a disk-shaped woody molding (H2) with a diameter of 53 mm and a thickness of about 5.5 mm (see FIG. 34). Various evaluations were then carried out. The results are shown in Tables 5 and 6.

[0103] Comparative Example 7 The same procedure as in Comparative Example 6 was carried out, except that the resin-impregnated material (X5) was replaced with the resin-impregnated material (X6) with a total mass of about 15 grams, to obtain a disk-shaped woody molding (H3) with a diameter of 53 mm and a thickness of about 4.5 mm (see FIG. 34). Various evaluations were then carried out. The results are shown in Tables 5 and 6.

[0104] [Table 5]

[0105] [Table 6]

[0106] From Table 6, it can be seen that the woody molded products obtained in Examples 13 and 14 have a superior woody texture and are warmer and softer than the woody molded product obtained in Comparative Example 7.

[0107] Here, in the paper "Thermal Properties of Wood and Contact Warmth" (Mokuzai Gakkaishi, Vol. 46 (2), p. 137-143) published by Obata et al., it is stated that thermal effusivity (the square root of the product of thermal conductivity, specific heat, and density) can be used as an index for evaluating the warmth of a material, and that the lower the thermal effusivity, the warmer the material. In Table 5, the thermal conductivity of the woody moldings (H1) and (H2) obtained in Examples 13 and 14 is lower than that of the woody molding (H3) obtained in Comparative Example 7, but in Table 6, the woody moldings (H1) and (H2) are judged to be warmer than the woody molding (H3), making it clear that the warmth close to that of wood is correlated with thermal conductivity.

[0108] 6. Complex Preparation In the following Example 15 and Comparative Example 8, a 4 mm thick (R: radial direction) Hinoki veneer (with density ρ a :0.47g / cm 3 ) was impregnated with an aqueous thermosetting phenolic resin solution with a solid content of 30%, dried at 35°C, and cut into a disk with a diameter of approximately 52 mm to obtain a resin-impregnated material (hereinafter referred to as "resin-impregnated material (X7)") with a melamine resin (solid content) content of 38 to 41%. A composite 51 (three-dimensional molded body) was produced by the method shown in Figure 35 using this resin-impregnated material (hereinafter referred to as "resin-impregnated material (X7)") and the following prepreg 41 as an adherend.

[0109] The prepreg 41 was produced as follows. As a raw material, a material obtained by cutting 30 g of a resin-impregnated plate before being made into a disk-shaped resin-impregnated material (X7) (before cutting) into 10 mm (L: fiber direction) x 10 mm (T: tangential direction) was used. This material was placed in a stacked state (thickness of the resin-impregnated material in the mold: about 35 mm) on the lower mold 33 arranged at the bottom of a mold 31 having a cylindrical cavity with an inner diameter of 53 mm, the same as in Example 1. Thereafter, the mold 31 was heated so that the temperature of the inner surface of the mold 31 was 100°C, and the mold 31 was pressed from above with a mirror-finished flat punch under a load of 50 tons (punch surface pressure: 225 MPa) for 30 seconds. Next, the heating of the mold 31 was stopped, and while maintaining the pressurized state, cooling water was circulated through the water channels in the mold to cool the molded product for 300 seconds, thereby producing a molded product having the desired general circular plate shape (diameter: 53 mm, thickness: approximately 13 mm).

[0110] Example 15 With the prepreg 41 placed on the lower die 33 disposed at the bottom of the die 31 (see FIG. 35(I)), a resin-impregnated material (X7) was placed on the surface of the prepreg 41 (see FIG. 35(II)). The total thickness of the prepreg 41 and the resin-impregnated material (X7) loaded in the die was about 17 mm. Next, the die 31 was heated so that the temperature of the inner surface of the die 31 reached 150° C., and a load of 10 tons (punch surface pressure: 45 MPa) was applied by the upper die 35, forming a precursor portion 46 (thickness: about 1 mm) between the upper die 35 and the lower die 33 (see FIG. 35(III)). After 10 seconds of compression, the upper mold 35 was moved upward for about 1.0 second while the precursor portion 46 was in contact with the inner surface of the upper mold 35, and the upper mold 35 was fixed at a point where the thickness of the material portion derived from the resin-impregnated material (X7) was about 2.3 mm. The thermosetting melamine resin was cured by maintaining the temperature (150°C) for about 110 seconds. Next, the heating of the mold 31 was stopped, and cooling water was circulated through the water passage in the mold to cool the molded product for 300 seconds. After that, the mold was removed to obtain a composite 51 having a desired thickness of 15.3 mm in which the adherend portion 42 derived from the prepreg 41 and the wood molded body portion 47 derived from the resin-impregnated material (X7) were joined (see FIG. 35(IV)).

[0111] 36 and 37 are images taken by a camera of the upper surface of the woody molded body portion 47 and the lower surface of the adherend portion 42 in the obtained composite 51, both of which had an excellent woody appearance. When the woody molded body portion 47 of the composite 51 was touched with the hand, it felt more like wood than like plastic.

[0112] Comparative Example 8 After achieving the state shown in Figure (II) in Example 15, the mold 31 was heated so that the temperature of the inner surface of the mold 31 reached 150°C, and a load of 10 tons (punch surface pressure: 45 MPa) was applied by the upper mold 35 for more than 120 seconds to harden the thermosetting phenolic resin. Thereafter, after cooling in the same manner as in Example 15, the mold was demolded to obtain a composite in which the adherend portion derived from the prepreg 41 and the wood molded body portion derived from the resin-impregnated material (X7) were joined.

[0113] Figures 38 and 39 are images taken by a camera of the upper surface of the woody molding part and the lower surface of the adherend part of the obtained composite, and both had an excellent woody appearance, but the grain of the wood material had been lost. In addition, when the woody molding part of the composite was touched with the hand, it felt similar to plastic.

[0114] 7. Manufacturing and evaluation of wood-based moldings (6) In the following Examples 16 and 17 and Comparative Example 9, bleached wood pieces (Japanese cypress or cedar) with a thickness of 10 mm or less (R: radial direction) were impregnated with a mixture obtained by adding polyalkylene oxide wax as a lubricant to an aqueous thermosetting melamine resin solution with a solid content concentration of 20% to a solution with a concentration of 3%. The resin-lubricant impregnated material (hereinafter referred to as "resin impregnated material (X8)") was obtained by drying at 35°C. The total content (solid content) of melamine resin and lubricant in this resin impregnated material (X8) was 34%, and the weight increase rate relative to the wood piece was 52%. Then, using a mold with a tray-shaped cavity of 158 mm x 135 mm, the resin impregnated material (X8) was processed to prepare a prepreg (hereinafter referred to as "prepreg (P)"), and this prepreg (P) was used to manufacture a tray-shaped wood molding.

[0115] The prepreg (P) was produced as follows. First, about 110 g of the resin-impregnated material (X8) was placed in a mold having a tray-shaped cavity. After that, the mold was heated so that the temperature of the inner surface of the mold was 110°C, and the mold was pressed from above with a mirror-finished punch under a load of 200 tons (punch surface pressure: 94 MPa) for 60 seconds. Next, the heating of the mold was stopped, and while maintaining the pressurized state, cooling water was circulated through the water channels in the mold to cool the molded product for 240 seconds, thereby obtaining a prepreg (P) having the desired tray-shaped general shape.

[0116] Example 16 Using the above mold and prepreg (P), a tray-type wood molded product (hereinafter referred to as "tray-type wood molded product (J1)") was manufactured based on the press schedule shown in FIG. The mold was heated so that the temperature of the inner surface of the mold was 165°C, and pressed from above with a mirror-finished punch at a load of 200 tons (punch surface pressure: 94 MPa), and this state was maintained for 30 seconds. Next, approximately 1.5 mm was unloaded, and the punch position was maintained. Note that the mold temperature was maintained at the same 165°C as above until 300 seconds had elapsed from the start of unloading, after which the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold until another 300 seconds had elapsed to cool the molded product. After that, the mold was demolded to obtain a tray-shaped woody molded product (J1) of the desired size of 158 mm x 135 mm and height of approximately 17 mm (thickness of the bottom surface: 2.8 mm), which contained a woody material made of coniferous wood, melamine cured resin, and a lubricant. The obtained woody molded product (J1) had the color of a piece of cypress wood, and when the surface was touched and its feel was evaluated, it was found to be good. FIG. 41 is a perspective image obtained by photographing one surface of this woody molded product (J1) with a camera.

[0117] In addition, the surface gloss of the obtained tray-shaped wood molding (J1) was measured using a Horiba Ltd. handheld gloss meter "Gloss Checker IG-331" (product name), and was found to be 30 in the longitudinal direction of the tray and 30 in the transverse direction (see Table 7).

[0118] Example 17 Using the above mold and prepreg (P), a tray-shaped wood molded product (hereinafter referred to as "tray-shaped wood molded product (J2)") was manufactured based on the press schedule shown in FIG. The mold was heated so that the temperature of the inner surface of the mold was 165°C, and the mold was pressed from above with a load of 200 tons (punch surface pressure: 94 MPa) using a mirror-finished punch, and this state was maintained for 30 seconds. Next, about 1.5 mm was unloaded, and the position of the punch was maintained for 30 seconds. After that, the mold was pressed from above with a load of 10 tons (punch surface pressure: 4.7 MPa) (load re-application process), and this load was maintained for 600 seconds. Note that the mold temperature was maintained at the same 165°C as above until 300 seconds had elapsed from the start of pressing in the load re-application process, after which the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold until another 300 seconds had elapsed to cool the molded product. Next, the mold was demolded to obtain a tray-shaped wood molded product (J2) of the desired size of 158 mm x 135 mm and height of about 16 mm (wall thickness of the bottom surface: 2.7 mm), which contained a wood material made of softwood, melamine cured resin, and a lubricant. The obtained woody molded product (J2) had the color of a piece of cypress wood, and when the surface was touched and evaluated, the feel was good. Figure 43 is an oblique image obtained by photographing one side surface of this woody molded product (J2) with a camera.

[0119] The surface gloss of the tray-shaped woody molded product (J2) was measured in the same manner as in Example 16, and was 45 in the longitudinal direction of the tray and 55 in the transverse direction (see Table 7), i.e., the surface gloss of the tray-shaped woody molded product (J2) was higher than that of the tray-shaped woody molded product (J1). Furthermore, when the unevenness of the surfaces of the woody molded product (J1) and the woody molded product (J2) was visually evaluated, the woody molded product (J2) was found to be smoother than the woody molded product (J1), indicating that the mirror shape of the die or punch was sufficiently transferred in the second method according to the present invention.

[0120] Comparative Example 9 Using the above mold and prepreg (P), a tray-shaped woody molded product (hereinafter referred to as "tray-shaped woody molded product (J3)") was manufactured based on the press schedule shown in FIG. The mold was heated so that the temperature of the inner surface of the mold was 165°C, and the mold was pressed from above with a mirror-finished punch at a load of 200 tons (punch surface pressure: 94 MPa), and this state was maintained for 600 seconds. The mold temperature was maintained at the same 165°C as above until 300 seconds had elapsed from the start of pressing, after which the heating of the mold was stopped, and cooling water was circulated through the water channel in the mold until another 300 seconds had elapsed to cool the molded product. The mold was then demolded to obtain a tray-shaped woody molded product (J3) of the desired size of 158 mm x 135 mm and height of about 16 mm (thickness of the bottom part: 2.5 mm), which contained a woody material made of coniferous wood, melamine-cured resin, and a lubricant. The surface of the obtained woody molded product (J3) was touched and its texture was evaluated, and the texture was poor, with no sense of woodiness being felt sufficiently. FIG. 45 is a perspective image obtained by photographing one surface of this woody molded product (J3) with a camera.

[0121] The surface gloss of the tray-shaped woody molded product (J3) was measured in the same manner as in Example 16, and was found to be 74 in the longitudinal direction of the tray and 64 in the lateral direction (see Table 7).

[0122] [Table 7] [Industrial Applicability]

[0123] The present invention is suitable for use in daily necessities, furniture and furnishings, building materials and construction components, electrical appliances or audio equipment casings, vehicle components (interior materials, etc.), and the like. [Explanation of symbols]

[0124] 10: Wooden molded body 12: Porosity measurement area of ​​wood cell lumen in included wood material 14: Porosity measurement area of ​​wood cell lumen at a deeper position than porosity measurement area 12 20: Woody cells 22: Cell wall 24:Ligny cell lumen 31: Mold 33: Lower mold 35: Upper type 41: Covered (プリプレグ) 42: The body part 45: Resin impregnated material 46: Front drive body 47: Wood forming part 51:Complex

Claims

1. A wood molded body comprising a wood material and a hardened resin, The wood material is derived from wood chips or wood boards, The cured resin is derived from a thermosetting resin, A woody molding having a grain, characterized in that, inside the woody molding, the porosity originating from the wood cell cavities of the wood material is 5 to 60%, and the difference in porosity between one region and another region located at different depths from the surface toward the inside is 15 points or less.

2. The wood molding according to claim 1, wherein the porosity originating from the wood cell cavities of the wood material inside the wood molding is 5 to 50%, and the difference between the porosity in a region having a depth of 0.01 mm to 1 mm from the surface of the wood molding and the porosity in a region having a depth of more than 1 mm from the surface of the wood molding is 11 points or less.

3. A method for producing the woody molded product according to claim 1 or 2, comprising the steps of: A resin-impregnated material preparation step of impregnating a wood raw material including wood chips or wood boards with a thermosetting resin to prepare a resin-impregnated material; a load application step of placing the resin-impregnated material in a mold and applying a load to the resin-impregnated material for 0.3 to 60 seconds; an unloading step of unloading the thermosetting resin contained in the resin-impregnated material in a compressed state within the mold before the thermosetting resin solidifies; a resin curing step of curing the thermosetting resin to obtain the woody molded body; 11. A method for producing a woody molded product having wood grain, comprising the steps of:

4. A method for manufacturing a wood molded body as described in claim 3, wherein in the load application process, a load is applied to the resin-impregnated material until the material becomes smaller than the wood molded body, and in the unloading process, the material in the mold is unloaded until it assumes the desired shape of the wood molded body.

5. The method for producing a woody molded product according to claim 3 or 4, wherein the load application step and the load removal step are carried out under heating conditions.

6. A method for producing the woody molded product according to claim 1 or 2, comprising the steps of: A resin-impregnated material preparation step of impregnating a wood raw material including wood chips or wood boards with a thermosetting resin to prepare a resin-impregnated material; a load application step of placing the resin-impregnated material in a mold and applying a load to the resin-impregnated material for 0.3 to 90 seconds; an unloading step of unloading the thermosetting resin contained in the resin-impregnated material in a compressed state within the mold before the thermosetting resin solidifies; a load reapplication step of applying a load to the resin-impregnated material before the thermosetting resin solidifies after the load is removed for 1 to 90 seconds from the end time of the load removal step; a resin curing step of curing the thermosetting resin to obtain the woody molded body; 11. A method for producing a woody molded product having wood grain, comprising the steps of:

7. A method for manufacturing a wood molded body as described in claim 6, wherein in the load application process, a load is applied to the resin-impregnated material until the material becomes smaller in size than the wood molded body, and in the unloading process, the material in the mold is unloaded until the material becomes larger in size than the desired wood molded body.

8. The method for producing a woody molded product according to claim 6 or 7, wherein the load application step, the load removal step, and the load reapplication step are carried out under heating conditions.

Citation Information

Patent Citations

  • Manufacture of lightweight wooden product

    JP1989171801A

  • Wooden resin molded article and material for it

    JP1999300711A

  • Compressed wood molding product

    JP2006289847A

  • Method for producing molding of vegetable material and molding obtained by the method

    JP2010155394A

  • Woody composite material and method for manufacturing the same

    JP2011020430A